Assessing impact of employee engagement on innovation and the mediating role of readiness for innovation. Issue 2 (9th July 2019) - Arshi, Tahseen; Rao, Venkoba
The causal relationship between employee engagement (EE) and innovation (INN) has of late received considerable academic attention, but research attempts to develop integrated model of EE and innovation is still fragmented. This research contributes to the existing literature by exploring the mediating role of readiness for innovation (RFI) between EE and INN. Data collected from 400 firms in the Sultanate of Oman were analysed using structure equation modelling. The findings indicate that employee engagement acts as significant predictor of innovation. Further, with the intervention of readiness of innovation factor, the predictability tends to be higher. Though a direct and positive relationship between employee engagement and innovation is established, an analysis of the indirect effects shows that readiness of innovation mediates this relationship. A comprehensive and an integrated model of employee engagement and innovation is developed and validated which advances knowledge in both the fields.